Đề xuất quy trình phát triển kỹ năng tự học cho học sinh phổ thông dân tộc nội trú - Nguyễn, Văn Đệ; Nguyễn, Thị Thu Hằng; Dương, Thị Hằng; Thiều, Văn Nam (Tạp chí Giáo dục, 2025)
General education does not only provide students with knowledge but also skills and attitudes, primarily represented in the four pillars of learning: learn to know, to do, to live with others and to be a human. Learning activities aim to develop students' qualities and competencies with basic, practical, modern knowledge and skills; at the same time, effective learning is demonstrated through the qualities of diligence, honesty, responsibility, helping students apply learnt knowledge and skills to solve problems in their studies and life even while still being at school. This study, through investigating the current status of management activities and contextual challenges related to students' self-study activities at 36 ethnic boarding schools in the Southern region of Vietnam, aims to answer the following questions: (1) What is the level of management of students' self-study activities at ethnic boarding schools? (2) How to improve the quality of students’ self-study activities at ethnic boarding schools in Vietnam?